FORMULATION AND EVALUATION OF ORAL SUSTAINED IN SITU GELLING SYSTEM OF ROXATIDINE - Mohammed Gulzar Ahmed; Chirag Kapoor; Sanjana A (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
Gel dosage forms are successfully used as drug delivery systems to control drug release and protect the medicaments from a hostile environment. The main objective of this present work is to formulate and evaluate in situ gels of roxatidine for the treatment of peptic ulcer. This system utilizes polymers that exhibit sol-to-gel phase transition due to change in specific physico-chemical parameters. In the present work in situ gels have been developed by using gellan gum and sodium alginate based on the concept of ion activated systems. Sol-to-gel transformation occurred in the presence of monovalent/divalent cations. Formulations were evaluated for clarity, drug content, in vitro gelling capacity, determination of pH, in situ release study, viscosity, gel strength, ex vivo gelation and stability study. All the results found to be satisfactory. Experimental part showed that viscosity of sols and gel strength was increased with increase in the concentration of polymers, also drug release gets sustaining. The formulations were therapeutically efficacious, sterile and provided sustained release of the drug over a period of time. These results demonstrated that the developed system is an alternative to conventional drug delivery systems and can improve patient compliance.Key words: In situ gels, Roxatidine, Peptic ulcer.